2021
DOI: 10.14417/ap.1859
|View full text |Cite
|
Sign up to set email alerts
|

Application of hypnosis in psychOncology: A review of the literature

Abstract: Hypnosis is useful for multiple somatic and psychological disorders, particularly cancer disease-related issues. In fact, the literature points out that hypnosis is effective in helping patients deal with aspects disease related, as well as in reducing the side effects of treatment. This review of the literature aims to summarize and assess the evidence of the usefulness of hypnosis in cancer patients and was conducted based on articles published between 2012 and 2019. The databases used were: B-on, SciELO, ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…There is a real public health issue in managing this distress in order to improve their quality of life and to enable them to live together at home for as long as possible [29,30]. This effect on the distress is in line with other studies on the use of clinical hypnosis in the field of health [45,[91][92][93][94][95][96][97] and continued three months after the intervention. The benefits of hypnosis could certainly be maintained and reinforced over time by encouraging daily practice with the audiotapes of the sessions.…”
Section: Helpfulness Of Interventionsupporting
confidence: 79%
“…There is a real public health issue in managing this distress in order to improve their quality of life and to enable them to live together at home for as long as possible [29,30]. This effect on the distress is in line with other studies on the use of clinical hypnosis in the field of health [45,[91][92][93][94][95][96][97] and continued three months after the intervention. The benefits of hypnosis could certainly be maintained and reinforced over time by encouraging daily practice with the audiotapes of the sessions.…”
Section: Helpfulness Of Interventionsupporting
confidence: 79%
“…A systematic review and meta-analysis has found hypnosis and therapeutic suggestion to be effective in chronic pain management (Adachi 2014). In cancer care, hypnosis reduces pain, anxiety, depression, fatigue and insomnia associated with treatments (Remondes-Costa 2021; Hayat 2022). It has been approved by the National Institute for Health and Care Excellence (NICE) as a treatment for irritable bowel syndrome (NICE 2017: recommendation 1.2.3), although mental health professionals, even those in the UK, are often unaware of this.…”
Section: An Omission From the Articlementioning
confidence: 99%